A psycholinguistic study of the bouba-kiki phenomenon: Exploring associations between sounds and shapes - Kasap, Süleyman; Ünsal, Firat (Lesya Ukrainka Eastern European National University, 2024)
This study investigates the cognitive phenomenon known as the bouba-kiki effect among English Language Teaching (ELT) students at Van Yüzüncü Yıl University in Turkey. The research aims to contribute to understanding how individuals intuitively associate specific sounds with abstract shapes, shedding light on the underlying cognitive processes of language perception. Participants (N=164) were presented with two abstract shapes and asked to match them with the pseudowords ‘bouba’ and ‘kiki’. Results revealed a significant preference (87.2%) associating the rounded shape with ‘bouba’ and the spiky shape with ‘kiki’. Additionally, participants were tasked with creating brand designs for ‘Kiki’ and ‘Bouba’, with 87.2% aligning their designs with their initial shape associations. Data analysis included descriptive statistics and a chi-square test, confirming a strong association between shape preferences and pseudoword assignment (χ²=132.05, p < .001). These findings underscore the robustness of the bouba-kiki effect across different cultural and linguistic contexts. This research contributes to interdisciplinary studies linking linguistics, psychology, and neuroscience, offering implications for language teaching methodologies and cognitive processing theories. By elucidating these associations, educators can enhance language learning strategies based on intuitive perceptual mechanisms.
Keywords: psycholinguistics; bouba-kiki effect; crossmodal perception; language cognition